Spices biotechnology - K V Peter (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
In recent times, biotechnological tools have supplemented various conventional approaches in conservation,characterization, improvement and utilization for increasing production and productivity of spices. In manyspices, viable micropropagation technologies are available for commercial production and generation of disease - free planting material. Somaclonal variation is important in crops where natural variability is low and a few useful somaclonal variants have been identified in ginger, turmeric and vanilla. Protoplast technology is also available for capsicum, black pepper, fennel, fenugreek, garlic, saffron and peppermint. In vitro cryopreservation, Synseed and Micro-rhizome technologies are available for safe propagation, conservation, movement, and exchange of spices germplasm. Studies are in progress for in vitro production of flavour and colouring compounds like capsaicin, vanillin, anethole, crocin, picrocrocin, saff'ranal, etc. using immobilized and transformed cell cultures. Use of molecular markers for crop profiling, fingerprinting, molecular taxonomy, identification of duplicate hybrids, estimation of genetic fidelity and tagging of genes for marker aided selection (MAS) is gaining importance. Isolation of important and useful genes and development of transgenics is in the preliminary stage.